2013
DOI: 10.1149/2.084308jes
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Factors on the Hydrolysis Reaction Rate of Some Para-Aminophenol Derivatives in Acidic pHs

Abstract: Electrochemical oxidation of some p-aminophenol derivatives (1–5) in acidic solutions has been investigated both experimentally and theoretically to provide insight into the influence of some factors on the hydrolysis reaction rate. The result of this work shows that the electrogenerated p-quinoneimines participate in the hydrolysis reaction and are converted to the p-benzoquinone. The hydrolysis reaction rate strongly depends on the structure of the p-aminophenols and solution's pH. In this work, the observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…and formation of 1oxH 2? in this condition cause increasing instability of produced p-quinonediimine [26,28]. In other words, using this data it could be concluded that in the intermediate pHs rate of the dimerization is faster than hydrolysis, and in the lower pH range the rate of the hydrolysis is faster than dimerization.…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…and formation of 1oxH 2? in this condition cause increasing instability of produced p-quinonediimine [26,28]. In other words, using this data it could be concluded that in the intermediate pHs rate of the dimerization is faster than hydrolysis, and in the lower pH range the rate of the hydrolysis is faster than dimerization.…”
Section: Resultsmentioning
confidence: 69%
“…Investigations indicated that dimerization, trimerization, hydrolysis, and hydroxylation can occur in electrochemical oxidation of amines which is highly dependent on pH of solution [24,25]. Along with our previous works in electrochemical study of amines [23][24][25][26][27][28], diversity of behavior in the electrochemical oxidation of 2,5-diethoxy-4-morpholinoaniline (2,5-DEMA, 1) at various conditions and also the importance of Schiff base reaction [29] prompted us to studying electrochemical oxidation of 2,5-DEMA at various conditions using cyclic voltammetry (CV) and controlled-potential coulometry. The results show that in all pHs electrochemically generated p-quinonediimine (1ox ?…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations